Lafaz Rahmah in the Quran - Nuraini Nuraini; Dhira Majid (Budapest International Research and Critics University, 2021)
In understanding the verses of the Quran, a comprehensive understanding is needed by looking at the interpretations of the scholars. In general, each expression has its own meaning. However, lafaẓ rahmah in the Quran has several sides of meaning. This will be a problem for the reader if the meaning is not explained properly. Thus the question arises of how to interpret lafaẓ rahmah in the Quran. It aims to describe the meaning of rahmah in the Quran based on its context by looking at the interpretation of scholars. The method used in this study is the mauḍū'i (thematic) method by collecting verses related to lafaẓ rahmah. The author uses a type of library research, namely by collecting library data and using descriptive analysis techniques on library materials. The results of the study concluded that lafaẓ rahmah in the Quran has a variety of meanings, according to the context of different verses, including: rahmah has the meaning of Islam, faith, heaven, rain, enjoyment, prophethood, the Quran, sustenance, help and victory, freedom from disaster, compassion, leniency, forgiveness, protection, 'Isa bin Maryam, Prophet Muhammad SAW, and taufik.